2000
DOI: 10.1096/fasebj.14.10.1464
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of neuronal 5‐lipoxygenase in an aging brain

Abstract: Aging is associated with increased incidence and/or severity of neurodegenerative pathologies. Oxygen‐mediated events are being considered as possible mechanisms responsible for the increasing neuronal vulnerability. Lipoxygenases are enzymes that, as cyclooxygenases (COX), can insert oxygen into the molecule of arachidonic acid and thereby synthesize inflammatory eicosanoids: leukotrienes [due to 5‐lipoxygenase (5‐LOX) activity] and prostaglandins (via COX activity). It appears that 5‐LOX is expressed in cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…58 There is a marked loss of 5-LOX immunoreactive cells in the pyramidal layer of the CA1 (Figs 3 and 4I-L) particularly in the LARD group which is consistent with our findings for the MAP2 antibody discussed above. Equally notable is the results for HSO fed animals which exhibit a loss of 5-LOX expression throughout the hippocampus.…”
Section: Discussionsupporting
confidence: 91%
“…58 There is a marked loss of 5-LOX immunoreactive cells in the pyramidal layer of the CA1 (Figs 3 and 4I-L) particularly in the LARD group which is consistent with our findings for the MAP2 antibody discussed above. Equally notable is the results for HSO fed animals which exhibit a loss of 5-LOX expression throughout the hippocampus.…”
Section: Discussionsupporting
confidence: 91%
“…5-lipoxygenase is a lipoxygenase present in the central nervous system 24 . Its up regulation in the NTS of the SHR together with the down regulation of LTB4-12-HD, the enzyme that causes dehydrogenation of LTB4 to 12-oxo-LTB4, could both cause the elevated levels of LTB4 that we found.…”
Section: Discussionmentioning
confidence: 99%
“…45,86,87 Levels of cyclooxygenase, lipoxygenase, prostanoids, and eicosanoids, all components of inflammatory pathways, have also been shown to be elevated in the brain with aging. 45,88,89 Furthermore, it has been shown that there is a progressive deterioration of the immune response with increased aging, including time to build a response, level of activation, and speed in which the response is ended. 9092 This altered immune response occurs in the periphery as well as in the brain.…”
Section: High-fat Diets and Cognitionmentioning
confidence: 99%